The effect of knowledge level on IUD contraceptive use in women of childbearing age - Yenny Okvitasari (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: The use of intrauterine device (IUD) contraception is one effective method for birth control and family planning. Despite this, IUD adoption rates among women of childbearing age are still relatively low. One factor that can affect IUD use is a woman's level of knowledge about this method of contraception. Objective: analyze the effect of knowledge level on IUD contraceptive use in women of childbearing age. Methods: This study used a quantitative research design with a cross sectional approach. The sampling technique uses Total Sampling and the number of respondents is 134 KB acceptors. Data collection using Knowledge questionnaire. Result: The results of the Chi Square statistical test showed a p value (0.001) < α = (0.05) with a confidence level of 95%, indicating that Ho was rejected and Ha was accepted or there was a knowledge relationship with IUD contraceptive use. Conclusion: The level of knowledge about IUDs has a significant effect on a woman's decision to use this method of contraception. Efforts to increase education and information about IUDs are expected to increase IUD use rates and help family planning programs.